HUBUNGAN PEMBERIAN ASI EKSKLUSIF DENGAN PERKEMBANGAN BAHASA AWAL ANAK USIA 6 BULAN - Rahmadhani, Nafia; Novayelinda, Riri; Utami, Gamya Tri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Exclusive breastfeeding during the first 6 months of birth has benefits for the development of children’s language. The purpose of this research is to identify the correlation between exclusive breastfeeding with early infant speech development 6 month. The design of this research is descriptive correlation study using cross sectional approach. The sample of this research is 57 respondents residing in the working area of Harapan Raya Puskesmas Pekanbaru using cluster sampling technique. The data is collected by using observation sheet of development 6 month old infant which was modified from ELM Scale 2 (Early Language Milestone Scale 2). The univariate analysis is used to know the frequency and bivariate analysis is using chi-square test. The results of this study shows that there is a relationship between the exclusive breastfeeding with the children early language development and the result of chi-square test shows that p value꞊ 0,013 <α꞊0,05, it can be conclude that there is significant correlation between exclusive breastfeeding with early infant speech development 6 month. Parents should give exclsive breastfeeding to their children, so development according to his age. Keywords : Breastfeeding, speech development , 6 month old infant, ELM Scale 2